Evaluation of video-based method for the measurement of reaction time in specific sport situation - Mudric, M.; Cuk, I.; Nedeljkovic, A.; Jovanovic, S.; Jaric, S. (International Journal of Performance Analysis in Sport, 2015)
The aim of the study was to evaluate a novel Video-based method for testing the reaction time (RT) in specific sport situations. The participants were elite karate kumite competitors and beginners. Two realistic responses (upper and lower blocks) under the conditions of known in advance (Simple RT condition) or unknown (Choice RT condition) realistic stimuli (video recordings of either a karate kick or punch presented in front of the subject) were recorded by a 3D motion analysis system. The tested RT proved to be highly reliable in both groups, for both responses, and under both conditions, although the indices of reliability could be higher in elite competitors. Moreover, the RT was consistently and markedly shorter in elite competitors than in beginners, as well as under the Simple RT than under the Choice RT conditions, independently of the stimulus. Together with the apparent face validity and relative simplicity, these findings strongly suggest that the evaluated method could both be used in future research and in routine testing of stimulus-response.